Prepletenost in nelokalnost v kvantni mehaniki - Ulčakar, Lara (Matrika, 2014)
In the article quantum entanglement and quantum nonlocality are presented. At the beginning quantum entanglement is explained via EPR paradox and later Bell's theorem. Later follows expanation of "No-Cloning" theorem, which is very important for discussion of the following theme - quantum teleportation. At the end latest experiments of quantum teleportation are described.
Keywords: kvantna mehanika; kvantna prepletenost; kvantna teleportacija; nelokalnost; nonlocality; quantum entanglement; quantum mechanics; quantum teleportation